Peirasmos and Dokimion in the New Testament: Contextual-Theological Analysis and Contemporary Implications - Wennar; Djone Georges Nicolas; Peter Oyugi (Sekolah Tinggi Teologi Real Batam, 2025)
This study investigates the Koine Greek terms peirasmos (temptation) and dokimion (testing) in the New Testament to clarify the widespread confusion among contemporary Christians regarding the origins, purposes, and theological significance of trials. Employing a qualitative method grounded in textual analysis, linguistic study, and hermeneutics, this research examines the etymology, distribution, and contextual use of both terms across selected New Testament passages. The study reveals that peirasmos frequently denotes a challenge that intends to weaken or disrupt faith, whereas dokimion refers to a refining test designed to strengthen and validate spiritual character. Nevertheless, the findings also show that peirasmos, when responded to in faith, can function as a means through which dokimion takes place, producing endurance and spiritual maturity. In light of contemporary challenges such as materialism, moral relativism, digital pressure, and identity fragmentation, this study demonstrates the relevance of these biblical concepts for shaping Christian responses to modern ethical and spiritual struggles. By integrating linguistic, historical, and contextual-theological analysis, this research provides a framework for understanding how believers can transform temptation into opportunities for growth and spiritual resilience. The study contributes to contextual theology by bridging biblical interpretation with practical implications for Christian life in a rapidly changing world. Keywords: crisis of faith; dokimion and peirasmos; modern era spirituality; spiritual maturity; weak loyalty Abstrak Penelitian ini mengkaji istilah Yunani Koine peirasmos (pencobaan) dan dokimion (ujian) dalam Perjanjian Baru untuk memperjelas kerancuan pemahaman di kalangan umat Kristen masa kini mengenai asal-usul, tujuan, dan signifikansi teologis dari berbagai tantangan iman. Dengan menggunakan metode kualitatif melalui studi linguistik, analisis teks, dan pendekatan hermeneutika, penelitian ini menelusuri akar kata, distribusi, serta konteks penggunaan kedua istilah tersebut dalam beberapa bagian Perjanjian Baru. Hasil penelitian menunjukkan bahwa peirasmos sering merujuk pada tantangan yang bertujuan melemahkan atau menjatuhkan iman, sedangkan dokimion menggambarkan proses pengujian yang dimaksudkan untuk memurnikan dan menguatkan karakter rohani. Temuan juga mengindikasikan bahwa peirasmos, apabila dihadapi dengan iman, dapat menjadi sarana bagi terjadinya dokimion yang menghasilkan ketekunan serta kematangan rohani. Dalam konteks modern seperti materialisme, relativisme moral, tekanan digital, dan krisis identitas, konsep-konsep ini terbukti relevan untuk membentuk respons Kristen terhadap pergumulan etis dan spiritual masa kini. Dengan mengintegrasikan analisis linguistik, historis, dan teologi kontekstual, penelitian ini memberikan kerangka untuk memahami bagaimana orang percaya dapat mengubah pencobaan menjadi kesempatan pertumbuhan rohani. Penelitian ini berkontribusi pada teologi kontekstual dengan menjembatani pemahaman biblika dengan tantangan praktis kehidupan Kristen kontemporer. Kata kunci: dokimion dan peirasmos; kematangan rohani; kesetiaan lemah; krisis iman; spiritual era modern